Primary School Teachers' Perspectives on ADHD in Alkadrow, Khartoum, Sudan - Zeinab Taha Ali Omer; Aya Hassan Abu Alhassan; Manal Mohammed Hassan Ahmed; Aida Ahmed Fadlala Ahmed; Suaad Ahmed Suliman Omer; Salma Mohammed Gomaa; Sameer Alqubati; Ahmed Abdalla Jarelnabe; Mohamed Abdalla Eltahir Hassan; Amal Abdelgadir Ali Mohamed; Mudathir Mohamedahmed Eltayeb; Amna Mohammed Idris; et al. (Sudan Journal of Medical Sciences, 2023)
Abstract Background: Attention deficit hyperactivity disorder, which is a prevalent neurodevelopmental condition, commonly manifests during early childhood and has the potential to adversely affect an individual's social, academic, and occupational performance in multiple settings. Students with ADHD may struggle with attention, focus, listening, and completing schoolwork. Additionally, they may exhibit restless or disruptive behavior in class and may have learning disabilities that affect their academic performance. The aim of this study was to explore the perspectives of primary school teachers on ADHD in Alkadrow, Khartoum, Sudan. Methods: A descriptive cross-sectional study was conducted in Alkadrow-Bahri locality, Sudan, over a period of three to six months in 2022. The study population included primary school teachers who had taught for at least one year and encountered at least one student with ADHD. A convenience sampling technique was used to select a minimum of 59 participants, and data were collected using a self-administered questionnaire with closed-ended questions. SPSS version 23 was used to analyze the data, including descriptive statistics and inferential statistics such as chi-square tests and logistic regression analysis. Results: The study had 59 participants, with the majority being female and in the age group of 41–45 years. The participants were mostly married and had obtained psychology courses, with a bachelor's degree being the most common level of education. Many participants had over 20 years of teaching experience. Regarding the attitude toward attention deficit hyperactivity, most participants strongly agreed that they did have a negative/positive attitude toward it, and a majority agreed or were neutral toward ADHD. However, in the case of attention deficit hyperactivity, a significant percentage of participants disagreed or strongly disagreed with the statement. Conclusion: The study found that most participants had a negative attitude toward student referrals for medical care and believed that most symptoms of ADHD can be lowered by aging. Additionally, more than half strongly disagreed that punishment has a positive effect on ADHD.